PVC Resin Supplier Selection with Integration of AHP and TOPSIS Methods - Frydella Krisna Putri; Farida Pulansari (Politeknik APP Jakarta, 2022)
Choosing the right suppliers is important for companies to provide raw materials for production in the long run. The sustainability of production activities is tightly controlled by suppliers in the manufacturing industry. A company in Mojokerto that manufactures PVC pipes falls under the plastic pipe industry sector. Raw materials for PVC resins must be ensured through assessments of suppliers. This study was conducted to determine which resin supplier was the best based on predetermined criteria. Variable include: price, quality, delivery, quantity accuracy, and service. To determine the order of preference for resin suppliers, this study uses AHP, which gives the individual a probability score for each criterion, and TOPSIS, which gives the user an indication of which supplier to choose when selecting a resin. As a result of data processing, suppliers are ranked based on their preferences. The preference values for each supplier are: supplier 1, which is 0.927; supplier 2, which is 0.739; supplier 3, which is 0.091; and supplier 4, which is 0.267. There are five parameters used in this study, and quality is known to have an influence of about 47% on the four suppliers. However, the delivery and service parameters only contribute 5%.